2016
DOI: 10.1021/acsnano.5b08218
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Functionalized Multi-Walled Carbon Nanotubes across Human Pulmonary Alveolar Epithelium: Dominant Role of Epithelial Type 1 Cells

Abstract: Uptake and translocation of short functionalized multi-walled carbon nanotubes (short-fMWCNTs) through the pulmonary respiratory epithelial barrier depend on physicochemical property and cell type. Two monoculture models, immortalized human alveolar epithelial type 1 (TT1) cells and primary human alveolar epithelial type 2 cells (AT2), which constitute the alveolar epithelial barrier, were employed to investigate the uptake and transport of 300 and 700 nm in length, poly(4-vinylpyridine)-functionalized, multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 51 publications
4
25
0
Order By: Relevance
“…There are several proposed reasons for why f-MWCNTs are taken up by epithelial cells. The first reason is the relative decrease in aggregation and the smaller size that results from carboxylation [ 14 , 34 ]. This study supports that conclusion with one caveat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several proposed reasons for why f-MWCNTs are taken up by epithelial cells. The first reason is the relative decrease in aggregation and the smaller size that results from carboxylation [ 14 , 34 ]. This study supports that conclusion with one caveat.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, surface charge and zeta potentials can be altered as a result of functionalization. Several studies indicate that this can make the particle variants more or less interactive with different cell types [ 15 , 16 , 34 ]. However, this may not appear to have been the case in this study, as there was no change in zeta potential with any MWCNT variant tested.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of multiwalled carbon nanotubes uptake with smaller length (300 nm) was higher than that of multiwalled carbon nanotubes with larger length (700nm). Even the translocation rates were different in the cell-type studied [48].…”
Section: Nanomaterials In the Service Of Biological And Biomedical Fimentioning
confidence: 93%
“…[298] Besides in vivo applications, CNTs have been used for high resolution mapping activities of single cells. [299, 300] In 2014, Fakhri et al observed a new intermediate mode of transport with the kinesin-1 motor proteins combined with SWNTs. [301] …”
Section: Theranostic Nanomaterialsmentioning
confidence: 99%